Acoustic porous metasurface for excellent sound absorption based on wave manipulation. (10th November 2018) - Fang, Yi; Zhang, Xin; Zhou, Jie
Abstract: Making use of the phase gradient method for diffracted wave manipulation, we propose an acoustic metasurface with a periodic structure backed with a rigid wall for sound absorption. The system consists of four slits filled with a metal-based fibrous material with various thicknesses in one period enabling a linear phase gradient of the reflected waves. The ability to manipulate the reflected waves using the designed metasurface is first validated by both simulations and experiments. Its oblique-incidence sound absorption performance is then studied at the frequency of interest. The broadband sound absorption property of the proposed metasurface is also evaluated within the frequency range from 500 Hz to 3500 Hz. The simulated and experimental results demonstrate that the designed metasurface possesses remarkable advantages in sound absorption capability compared with the individual porous elements. This study provides an effective method to enhance the sound absorption performance of uniform porous materials. The proposed metasurface has a good potential to be applied for sound absorption in practice.